Storybird as a tool for activating foreign languagelearners - RUSEK, BEATA (Glottodidactica, 2017)
Boredom, monotony and inactivity are some causes of passive learner behaviours during foreign language classes. A teacher who is aware of the importance of the learning process has to be consciously responsible for activating learners. New technologies offer numerous opportunities. The tool presented in this article: Storybird, allows learners to create and publish their own illustrated stories. Differences between traditional writing tasks versus using Storybird are discussed here. Analysis of a survey allows us to see the potentil of this tool from the learner perspective.